COMMON FIXED POINT THEOREMS FOR WEAKLY COMMUTING MAPPINGS IN GENERALIZED INTUITIONISTIC FUZZY METRIC SPACES - JEYARAMAN, M.; POOVARAGAVAN, D. (International Journal of Mathematical Archive, 2018)
In this paper, we prove a common fixed point theorems for compatible and weakly commuting maps in generalized intuitionistic fuzzy metric spaces.